BRIDGING NATURE AND CITIES: HARNESSING ECOSYSTEM SERVICES FOR URBAN REGENERATION - Naaz, Shaila; Mehrotra, Nirmita (International Journal of Research -GRANTHAALAYAH, 2024)
This research paper tries to highlight the importance of the study and analysis of ecosystem services. This paper talks about knowledge of the ecosystem and its utilization for the regeneration of an urban system. These goals are going to be measurable and are based on real situations of the specific site. The system is going to be coined as an analysis of ecosystem Services. The study is crucial because due to rural-to-urban migration, exponential growth in population, and many more factors, the cities are getting huge populations to deal with. These growths have shown many negative impacts on the ecology and ecosystem of the urban areas., The dependency on the ecosystems for survival makes the ecosystem very prone to degradation in quality as well as quantity. Global warming, drastic climate changes, depletion of the ozone layer, and reduction of biodiversity make this topic incredibly significant to study so that we have tools to regenerate our urban areas. The focus of the study is not only to identify but also quantify them, with relevance to cities in India. It is exceedingly difficult to generalize this topic and to go ahead with a “one size fits all “approach. Every city in the world is different and reflects the importance of ecosystem services in a different manner. The ecosystem services and their significance vary from city to city. Cities are vastly different because of the factors that make a city. For example; sociologically the cities have hugely different demographics. They have socio-cultural differences, and the size and area of the cities vary from small cities to urban agglomerations. They have climatic and geographical differences. The paper is concluded with the identification of the ecosystem services and how to utilize them for the regeneration of an urban area.